Efficacy of transcutaneous electric nerve stimulation over systemic pharmacotherapy in the management of temporomandibular joint disorders - A systematic review and meta-analysis - Indra Gopi; Gopal Maragathavalli; T N Uma Maheshwari (Wolters Kluwer Medknow Publications, 2021)
Temporomandibular disorders (TMDs) encompass numerous clinical complications that involve the temporomandibular joint (TMJ), masticatory musculature, and its associated structures, or both. Abundant research in this field has been conducted; however, there is no conclusive evidence reported in the effective management of TMD using physical therapy such as Transcutaneous Electric Nerve Stimulation (TENS). The systematic review and meta-analysis aimed to compare and evaluate the efficacy of transcutaneous electric nerve stimulation over systemic pharmacotherapies in the management of symptomatic patients with temporomandibular joint disorders. The present review has been registered with PROSPERO - An international prospective register of systematic review (CRD42021233019). An electronic search was done in PubMed, Cochrane Library, Science Direct, Google Scholar, Latin American and Caribbean Health Sciences Literature (LILACS), ClinicalTrial.gov, and sci-hub.se. Manual electronic searches were also carried out and articles were handpicked. The assessments of articles were done using selection criteria. There are a vast number of studies done in this subject of interest and hence, only prospective clinical trials like Randomized clinical trials (RCTs) and controlled clinical trials (CCTs) were included in this review. A total of three studies were included in this review, which consisted of prospective RCTs and CCTs. Two studies have been reported for meta-analysis. The included studies show TENS is proven to be effective in the management of TMD. The currently available evidence was insufficient to conclude the effectiveness of transcutaneous electric nerve stimulation and systemic pharmacotherapies in temporomandibular joint disorders. Based on the results of the meta-analysis, we can conclude that there was a significant reduction in pain encountered due to TENS.